Area-Selective Atomic Layer Deposition on Homogeneous Substrate for Next-Generation Electronic Devices - Rhee, Min Jeong; Won, Byoungjun; Lim, Young Jin; Song, Jeong Gyu; Kim, Sunghyun; Oh, Il Kwon (Advanced Science, 2025)
Area-selective atomic layer deposition (AS-ALD) has focused on controlling the promotion or blocking of precursor molecules on “heterogeneous” surfaces comprising different materials. This study proposes a new concept of AS-ALD on “homogeneous” surfaces comprising a single material. In this work, a homogeneous ZrO2 substrate is selectively fluorinated using sulfur hexafluoride (SF6) gas. The SF6 decomposes and incorporates into oxygen vacancies in ZrO2, forming F-terminated surface at grain boundaries (GBs). In the following step, the remaining hydroxyl-terminated ZrO2 areas are blocked by a cyclopentadienyl ligand to prevent aluminum precursor adsorption. Density functional theory and Monte Carlo simulations show that selectively passivated GBs of ZrO2 lead to the selective adsorption of ZrCp(NMe2)3 inhibitors. Selective growth of Al2O3 along GBs of ZrO2 is observed by elemental mapping from transmission electron microscopy. Finally, GB-selective Al2O3 increases overalldielectric constant by 15.5% in ZrO2/Al2O3/ZrO2 stacks with no increase in leakage currents, showing that the GB-selective Al2O3 incorporation suffices to passivate leakage paths through ZrO2 GBs. These findings provide fundamental guidelines for performing AS-ALD on homogeneous surfaces and highlight the potential of this approach for applications in next-generation electronic devices.
Keywords: current; Area selective; Area-selective atomic layer deposition; Atomic-layer deposition; Blockings; Electronics devices; Grain-boundaries; Homogeneous substrates; Homogeneous surfaces; ZrO 2; area-selective atomic layer deposition; dielectric; grain boundary; homogeneous surface; leakage currents